Numerical Investigation on Time-Dependent Deformation in Roadway - Yuantian Sun; Guichen Li; Junfei Zhang; Bicheng Yao; Deyu Qian; Jiandong Huang (Advances in Civil Engineering)
The roadway deformation normally relates to time especially for underground coal roadway. The strength of soft coal is low, and therefore the deformation increases gradually under constant stress with time, which is called rheology deformation. In this study, based on a field case, the rock mass properties and deformation data of the roadway were obtained according to the field test. A 3D numerical model was then established, and the rheological deformation including horizontal and vertical deformation of the coal roadway was systematically analyzed. The results showed that the rheological deformation of horizontal sidewall accounts for almost 30% of the whole deformation, and the stable time for such roadway is around 60 days after excavation. The tendency of the roof deformation is similar to the sidewalls, and however, the floor deformation is different. Then the related suggestions for maintaining the stability of such roadway were proposed, which is useful in-field application.